MEKANISME PENYELESAIAN SENGKETA KONSTRUKSI MENURUT UNDANG-UNDANG NOMOR 2 TAHUN 2017 TENTANG JASA KONSTRUKSI - Priyambodo, Mas Agus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
In essence, construction projects arise because of the convergence of two interests.On the one hand, there is a demand (demand) from the Service User, on the other hand the Service Provider offers its service (offer). Therefore, law number 2 of 2017 concerning Construction Services in Article 1 Paragraph (5) and (6) defines Service Users as owners or employers who use Construction Services, while Service Providers are providers of Construction Services. Construction is a very complex industry, this is because in construction projects there are multiple disciplines and dealing with many people who have their own interests. This condition also opens up opportunities for greater disputes. Disputes in construction work contracts or construction disputes are events that sometimes arise and cannot be avoided in the execution of the contract. The causes of this also vary from both internal and external factors. The problem in this paper is howto resolve construction disputes according to law number 2 of 2017 concerning construction services. The research used is normative legal research, which relies on secondary data as the main data source. The results showed that after the issuance of Law no. 2/2017 concerning Construction Services, construction disputes must first be resolved through deliberation for consensus. If the disputing parties do not find an agreement, then the settlement is taken through the stages ofdispute resolution as regulated in the construction work contract. Then if the dispute resolution is not stated in the construction work contract, then the parties with written approval will regulate the dispute resolution procedure chosen.